Hubungan Kekerabatan Kakatua (Psittaciformes) Berdasarkan Gen Cytochrome C Oxidase Subunit I (COI) secara In-silico - Pharmawati, Made; Rosiana, I Wayan (Journal of Natural Sciences, 2024)
Cockatoos are member of the order Psittaciformes. Indonesia have eight endemic species of  Cockatoos including : Black Palm Cockatoo (Probosciger aterrimus), Moluccan Cockatoo (Cacatua moluccensis), Tanimbar Cockatoo (Cacatua goffiniana), White Crested Cockatoo (Cacatua alba), Galerita or Triton Cockatoo (Cacatua galerita), Little Corella Cockatoo (Cacatua sanguinea ), Lesser Cockatoo (Cacatua sulphurea) and Citroon Cockatoo (Cacatua sulphurea citrinocristata). Genetic studies are currently considered an appropriate method for studying species relationships. This research aimed to determine the relationship of endemic Indonesian Cockatoos genus Cacatoa using COI gene in silico. The COI gene sequence for each individual cockatoo was accessed through National Center for Biotechnology (NCBI) data, sequence alignment and phylogenetic tree reconstruction using software mega version 11. The results of the phylogenetic tree reconstruction showed that the Indonesian endemic cockatoogenus Cacatoa were grouped into three clusters. The three clusters were the cluster of C. galerita and C. sulphurea, the cluster of C. goffiniana and C. sanguinea, and the cluster of C. alba and C. moluccensis.